The Analysis of Women’s Decision to Work on Sandwich Generation in Indonesia - Mauri, Mahesa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The Sandwich Generation refers to individuals of working age who are simultaneously responsible for raising their own children and caring for their aging parents, a dual responsibility that presents numerous challenges. This burden is particularly significant for women in Indonesia, where cultural expectations often require them to prioritize family caregiving over professional careers. Many Sandwich Generation women face difficult choices between raising their children, maintaining employment, and providing financial support for both their children and elderly parents. Using data from the 2014 Indonesia Family Life Survey (IFLS) by probit regression, it is known that the responsibilities of being in the Sandwich Generationsignificantly impact women's decisions to work. This finding underscores the need for policies that support women who are balancing these dual roles, particularly in creating environments that enable them to participate in the workforce while fulfilling their caregiving duties. Implementing such policies could greatly enhance the quality of life for these women by reducing the strain of managing work and family responsibilities. Based on this research, sddressing the needs of the Sandwich Generation is crucial for fostering a more inclusive and supportive societal framework in Indonesia. Abstrak Generasi Sandwich merujuk kepada individu usia produktif yang secara bersamaan bertanggung jawab untuk membesarkan anak-anak mereka sendiri dan merawat orang tua yang sudah lanjut usia. Tanggung jawab ganda ini menciptakan berbagai tantangan bagi generasi sandwich, terutama bagi wanita Sandwich Generation yaang dihadapkan pada pilihan antara membesarkan anak atau bekerja untuk memberikan dukungan finansial baik untuk anak-anak maupun orang tua mereka yang sudah tua. Analisis data dari Survei Kehidupan Keluarga Indonesia (IFLS) tahun 2014 menggunakan regresi probit menunjukkan bahwa tanggung jawab sebagai bagian dari Sandwich Generation memiliki dampak signifikan terhadap keputusan wanita untuk bekerja. Temuan ini menekankan perlunya kebijakan yang mendukung wanita yang harus menyeimbangkan peran ganda ini, khususnya dalam menciptakan lingkungan yang memungkinkan mereka untuk berpartisipasi dalam angkatan kerja. Temuan yang telah ada menyiratkan bahwa perlu adanya kebijakan bagi perempuan sandwich generation yang dapat memudahkan mereka untuk bekerja guna meningkatkan kualitas hidup mereka. Memperhatikan kebutuhan wanita Sandwich Generation sangat penting untuk mendorong kerangka sosial yang lebih inklusif dan mendukung di Indonesia.